Transnational Religious Tourism in Modern China and the Transformation of the Cult of Mazu - Zhang, Yanchao (Religions, 2021)
This article explores transformations in the worship of popular goddess Mazu as a result of (religious) tourism. In particular, it focuses on the role of transnational tourism in the invention of tradition, folklorization, and commodification of the Mazu cult. Support from the central and local governments and the impact of economic globalization have transformed a traditional pilgrimage site that initially had a local and then national scope into a transnational tourist attraction. More specifically, the ancestral temple of Mazu at Meizhou Island, which was established as the uncontested origin of Mazu’s cult during the Song dynasty (960 to 1276), has been reconfigured architecturally and liturgically to function as both a sacred site and a tourist attraction. This reconfiguration has involved the reconstruction of traditional rituals and religious performances for religious tourism to promote the temple as the unadulterated expression of an intangible cultural heritage. The strategic combination of traditional rituals such as “dividing incense” and an innovative ceremony enjoining all devotees of “Mazu all over the world [to] return to mother’s home” to worship her have not only consolidated the goddess as a symbol of common cultural identity in mainland China, but also for the preservation of Chinese identity in diaspora. Indeed, Chinese migrants and their descendants are among the increasing numbers of pilgrims/tourists who come to Mazu’s ancestral temple seeking to reconnect with their heritage by partaking in authentic traditions. This article examines the spatial and ritual transformations that have re-signified this temple, and by extension, the cult of Mazu, as well as the media through which these transformations have spread transnationally. We will see that (transnational) religious tourism is a key medium.